## Simplifying (6u)^2

In mathematics, simplifying expressions is a crucial skill. Let's break down how to simplify the expression **(6u)^2**.

### Understanding the Concept

The expression **(6u)^2** represents **6u multiplied by itself**.

**(6u)^2 = (6u) * (6u)**

### Applying the Exponent Rule

To simplify, we utilize the rule of exponents, which states: **(a * b)^n = a^n * b^n**.

- Applying this rule, we get:
**(6u)^2 = 6^2 * u^2**

### Final Result

**6^2 = 36**and**u^2 = u * u**- Therefore, the simplified expression is
**36u^2**.

### Conclusion

By applying the exponent rule, we can simplify **(6u)^2** to **36u^2**. Remember to square both the numerical coefficient and the variable.